Comparison between oral pentoxifylline + corticosteroid andoral corticosteroid alone for severe erythema nodosum leprosum - Martinus, Martinus; Rihatmadja, Rahadi; Menaldi, Sri Linuwih (UI Scholars Hub, 2022)
Background: Severe erythema nodosum leprosum (ENL) is common but difficult to treat. Long term use of systemic corticosteroid causes side effects. This study compares the use of a combination of pentoxifylline + oral corticosteroids with a single oral corticosteroid in leprosy patients with severe ENL reactions. Parameters measured include skin RSA score, systemic RSA, total corticosteroid dose, resolution time of skin lesions, improvement of pain VAS and treatment side effects.Methods: 29 subjects with severe ENL reactions are allocated randomly into two groups which receive oral pentoxifylline + methylprednisolone, and oral placebo + methylprednisolone for 12 weeks. The starting dose of pentoxifylline are 400 mg thrice daily for 4 weeks, tapered to 400 mg daily every 4 weeks. Methylprednisolone is based on WHO guideline. Results: In the end, the median of cutaneous RSA score in pentoxifylline vs placebo group is 4 (0-5) vs 3 (0-5). The median of systemic RSA score in pentoxifylline vs placebo group is 0 (0-6) vs 0 (0-5). The median of total corticosteroid doses in pentoxifylline vs placebo group is 156 (120-200) mg vs 136 (96-200) mg. The median of resolution time in pentoxifylline vs placebo group is 6 (0-12) weeks vs 6 (0-12) weeks. The median of change of pain VAS score in pentoxifylline vs placebo group is 5 (0-6) vs 3 (-3-6). No statistically significant difference (p>0,05) are found in all parameters, including side effects. Conclusion: Combination of oral pentoxifylline + corticosteroid is not proven to be more effective. Both are safe.